Efek Pupuk Organik Kascing dan Pupuk Organik Cair (POC) Turi (Sesbania Grandiflora L.) Terhadap Pertumbuhan dan Hasil Tanaman Selada Merah (Lactuca Sativa L.) - Harlina Kusumatuti; Aditiameri Aditiameri; Engkom Badriah (Agrisia: Jurnal Ilmu-Ilmu Pertanian, 2024)
Red lettuce is a type of vegetable that has commercial value and fairly high prospects. The selling value of red lettuce is higher than other varieties of lettuce, judging from the anthocyanin content in it is very beneficial for health. Vermicompost is an organic fertilizer derived from the feces or feces of earthworms. Vermicompost on the soil can improve soil properties such as improving structure, porosity, permeability, increasing the ability to hold water. is a Liquid Organic Fertilizer (POC) derived from natural plants such as turi leaves (Sesbania grandiflora L.) which has a high Nitrogen (N) content and complete micro and macro nutrients. This study aims to determine the ability and effectiveness of the use of vermicompost organic fertilizer and Turi Liquid Organic Fertilizer (POC) (Sesbania grandiflora L.) on the growth and production of red lettuce plants, which was carried out at Kp. Tegal kihiang, RT 005/RW 003, Karangindah Village, Bojongmangu District, Bekasi Regency, for 3 months November-December 2023. This study used Randomized Group Design (RAK). In this experiment, 4 doses of vermicompost fertilizer and 4 doses of POC TURI (4X4) were used. Where there are 16 experimental units that are repeated 4 times. Total plants studied 64 plants. Data analysis using a 5% DMRT test using SPSS application version 24. The results showed that the interaction on each age parameter of 7 HST, 14 HST, 21 HST, 28 HST, 35 HST, and 42 HST was not significantly different, however, in each treatment there was a real effect. Plant height and number of leaves had a significant influence on vermicompost fertilizer at the age of 21 HST and 42 HST, while on the application of POC Turi there was a real influence on the age of 14 HST, 35HST, and 42 HST. Parameters of leaf width, stem diameter and wet weight of plants showed a marked or significant difference at the age of 42 HST in all treatments